Narrating Perinatal Obsessive-Compulsive Disorder Through Blogs. Issue 5 (September 2022) - Beck, Cheryl Tatano
Abstract: Purpose: To describe women's experiences of perinatal obsessive-compulsive disorder (OCD) as written in their blogs. Study Design and Method: This qualitative descriptive study examined perinatal OCD blogs identified using Google search engine. Krippendorff's thematic content analysis method for qualitative data was used. The unit of analysis included segments of the bloggers' descriptions of their perinatal OCD. Clustering and dendrograms were used to group the data into themes. Results: Forty-three different posts from women in the United Kingdom, United States, Australia, and South Africa were analyzed. Five themes were identified that described women's experiences of perinatal OCD as told in their blogs: (1) Starting to tighten its grip during pregnancy, (2) Keeping horrific secrets all to themselves, (3) Tortured with terrifying images and thoughts, (4) Driven to compulsive behaviors to protect their infants, and (5) Long difficult road to recovery but so worth it. Clinical Implications: Perinatal OCD is a hidden problem that can have negative consequences for mothers and for their infants and families if not diagnosed or if misdiagnosed. There are effective treatments for OCD, but first nurses and other health care providers need to identify the women who are struggling with this anxiety disorder. During the perinatal period nurses can screen women for OCD. Developing a trusting relationship with pregnant and postpartum women is critical for nurses so that their patients can feel safe enough to share their horrific secret thoughts. Abstract : Perinatal obsessive-compulsive disorder is an often hidden anxiety disorder that can have negative consequences for mothers and for their infants and families if not diagnosed or if misdiagnosed. In this study, blog posts of mothers in the United Kingdom, United States, Australia, and South Africa with obsessive-complusive disorder were reviewed and themes identified. Developing a trusting relationship with pregnant and postpartum women is critical for nurses so that their patients can feel safe enough to share their experiences with obsesssive-complusive disorder and appropriate referral and treatment can be initiated.